The hydrogel of Mangosteen Peel (Garcinia Mangostana L.) To Improve Wound in Perineal among Postpartum - Ananti Setya Primawati Putri; Melyana Nurul Widyawati; Suryati Kumorowulan (International Journal of Nursing and Health Services (IJNHS), 2020)
This study aimed to examine relationship between age, sex, type of stroke, admission time, frequency of attacks, comorbidities, and muscle strength with functional abilities among stroke patients. A cross-sectional was applied in this study. The findings showed that there was relationship between muscle strength and functional ability among stroke patients. However, there is no relationship between age, type of stroke, commorbidities, and experience of stroke attack with functional ability among stroke patients. Inconclusion stroke is a major cause of functional disorders Keyword: mangosteen peel hydrogel, wound healing, perineal, postpartum women